1999
DOI: 10.1518/001872099779577354
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Spatial Facilitation of Visual Search Performance: Effect of Cue Precision and Distractor Density

Abstract: Two experiments examined auditory spatial facilitation of visual search performance under conditions varying in auditory cue precision and visual distractor density. The auditory cue was spatially coincided with the target, was displaced from the target by 6°, or was uninformative. Distractors were manipulated globally (throughout the field) and locally (within 6.5° of the target) separately at densities of 0%, 20%, and 80%. In Experiment 1, auditory cue precision was constant and distractor densities varied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
5
26
1
Order By: Relevance
“…Thus, one might argue that the uninformative cues were actually more closely aligned with the spatial location of the visual targets than were the informative cues. Rudmann and Strybel (1999) found that the search latencies for visual targets were significantly higher when far from the participants' body. On the basis of this line of reasoning, the facilitation of participants' visual search performance should be larger in the latter case (i.e., when the cue and target originate from the same distal region of space).…”
Section: Tion ( 38) There Was No Significant Effect Of Cue Type [F(mentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, one might argue that the uninformative cues were actually more closely aligned with the spatial location of the visual targets than were the informative cues. Rudmann and Strybel (1999) found that the search latencies for visual targets were significantly higher when far from the participants' body. On the basis of this line of reasoning, the facilitation of participants' visual search performance should be larger in the latter case (i.e., when the cue and target originate from the same distal region of space).…”
Section: Tion ( 38) There Was No Significant Effect Of Cue Type [F(mentioning
confidence: 88%
“…However, the limitations of screen size, clutter, and human auditory localization ability do not appear to hinder the potential advantages of spatially colocalized auditory cues under such conditions. Rudmann and Strybel (1999) investigated whether the presentation of auditory cues that were spatially coincident, displaced by 6º, or else spatially uninformative with regard to the location of the visual target would facilitate participants' visual search performance. d Although spatially coincident auditory cues were found to be most effective in terms of reducing participants' visual search latencies, the displaced auditory cues were n still effective in terms of enhancing visual search when compared with performance in the uninformative-cue condition.…”
mentioning
confidence: 99%
“…Auditory and tactile cues have also been shown to influence visual search. This has been shown when the auditory or tactile cue was spatially informative (Bolia, D'Angelo, & McKinley, 1999;Jones, Gray, Spence, & Tan, 2008;Rudmann & Strybel, 1999), when the auditory or tactile cue was temporally synchronous with a change in color of the target (Ngo & Spence, 2010;Van der Burg, Cass, Olivers, Theeuwes, & Alais, 2010;Van der Burg, Olivers, Bronkhorst, & Theeuwes, 2008b, Van der Burg, Olivers, Bronkhorst, & Theeuwes, 2009Zannoli, Cass, Mamassian, & Alais, 2012) and when the auditory cue was semantically congruent with the target object (Iordanescu, Grabowecky, Franconeri, Theeuwes, & Suzuki, 2010;Iordanescu, Gravowecky, & Suzuki, 2011;Iordanescu, Guzman-Martinez, Grabowecky, & Suzuki, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown repeatedly, (e.g., Rudmann & Strybel, 1999) that the presence of a simple auditory cue spatially coincident with a visual target can reduce the time required to locate and identify a visual target. The magnitude of the search time reduction depends on many visual factors such as search field size, target distance and distractor density.…”
Section: Virtual Auditory Warningsmentioning
confidence: 99%